Developing Inclusive Values and Character: A Systematic Literature Review on Education Strategy in Religious-Based Social Conflicts - Siswantara, Yusuf (LP3MKIL, 2024)
The diversity of society is the wealth of a nation, but it can also be a source of social conflict. Value education becomes a strategy for developing inclusive character. Educational research indicates the urgency of inclusive values and character as a strategy for addressing exclusive values in religious-based social conflicts. To explore scientific research on inclusive values, a systematic literature review was conducted as a research methodology. The SLR focused on seven questions, including research, publication trends, publication patterns, backgrounds, institutional involvement, methods, and implications of inclusive values for education. The research results highlighted the problems in this field and provided three important recommendations for the development of inclusive values and character as a strategy for education in religious-based social conflicts. These recommendations can be used as a reference in building an inclusive, tolerant, and peaceful society.